Developing an e-commerce website for enhancing customer sales - Lee, Yik Fei (2020)
E-Commerce, a well-known term that had led the world to another level in many sectors such as business, industrial, logistics, etc. As a millennial myself that had been using the Internet for over a decade, it was not a doubt for me to agree that E-Commerce brought a lot of impacts around the globe. The demand for better services in E-Commerce had also kept increasing and it was caused by the serious and harsh competitive environment between all the E-Commerce platforms since it was an effective way to enhance sales. To maximize the profit gained from a particular E-Commerce website, the purpose and objectives of this project were discovered. The highlight of this project was the “shop virtually” feature development. This feature was discovered by the idea of providing unique and interesting experiences for uses while shopping using this website. “In computing, virtual is a digitally replicated version of something real. The replication, which is created with software, may not be an exact copy of the actual item, but it is similar enough in essence to be described as a digital rendition.” (Margaret Rouse, 2015). Hence, this shopping virtually feature provided a virtual environment like how people went shopping in the malls. It was just that they were to control a 2-D digital controlling character to shop in a game. Moreover, there were also built in mini games for users to get highest score in exchange for vouchers while shopping in this website.